"We are not aliens": Exploring the Meaning of Disability and the Nature of Belongingness in a Fourth Grade Classroom - Priya Lalvani (Disability Studies Quarterly, 2015)
In this narrative essay I describe the process and outcomes of a group of fourth graders' engagement in a critical inquiry into the constructed meaning of disability in society. Through self-directed and guided learning, these students examined the historical roots of disability oppression and deconstructed ableist assumptions, and thus found their own understanding about community membership to be transformed. Positioning the need to infuse disability history in schools as an imperative, this paper invites disability studies scholars and social justice educators alike to confront the silences around the topic of disability in schools and to create spaces for children to engage in meaningful dialogues about society's responses to human differences.
Keywords: social justice education; disability history; ableism; inclusion; disability; critical pedagogy